(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a telerehabilitation program in patients following anterior cruciate ligament reconstruction of the knee joint. Subjects and methods: A quasi-experimental controlled study with pre- and post-intervention assessments was conducted on 50 patients post-anterior cruciate ligament reconstruction from November 2024 to July 2025. Participants were divided into 2 groups: conventional rehabilitation (n = 25) and telerehabilitation via the OpenTeleRehab application (n = 25). The numeric rating scale (NRS) for pain, knee range of motion (ROM), and the international knee documentation committee (IKDC) subjective knee evaluation form were assessed at baseline and after 4 weeks of intervention. ANCOVA was utilized to adjust for baseline differences in knee flexion ROM. Results: After 4 weeks, no statistically significant differences were observed between the two groups regarding improvements in NRS, IKDC scores, or knee extension ROM (p > 0.05). Notably, after adjusting for baseline values, the telerehabilitation group showed significantly greater improvement in knee flexion ROM compared to the conventional rehabilitation group (46.60° ± 14.84° vs 24.00° ± 17.14°; p = 0.048). Conclusion: Telerehabilitation is an effective and feasible approach during the early phase after anterior cruciate ligament reconstruction, yielding functional and range-of-motion improvements that are comparable to or better than conventional methods.